The world sorghum and millet economies: Facts, trends and outlook - FAO (FAO, 1996)
This book reviews the current structire of the world economies of the two crops and analyses the supply and demand situations, both current and projected. It also examines the major constraints to production of sorghum and millet and policy options that could help increase the output and quality of these crops throughout the semi-arid tropics